Pola Aktivitas Pengunjung Terhadap Ruang Terbuka Publik Pada Kawasan Pantai Melasti, Bali - Putu Gede Wahyu Satya Nugraha; I Ketut Sugihantara (JAUR (JOURNAL OF ARCHITECTURE AND URBANISM RESEARCH), 2022)
Melasti Beach was used as the object of research because it has a high level of visits, recorded during January and February 2021, the number of visitors who came to Melasti Beach was 86,214 people. The density of beach visitor activities and the existence of religious ritual activities in it are considered to represent the pattern of visitor activity in public open spaces. Seeing the high number of visits, the author is interested in conducting this research to find out what activities are taking place in it and also the pattern of activities in it. This aims to obtain a pattern of circulation of activities that take place in the research location to be a reference for designers in planning public open space facilities. The theory used in this research is behavior setting, which is studying the relationship between human behavior and the environment that accommodates these activities. The method of data collection is by observing the movement patterns of visitor activities and interviews and using questionnaires distributed to people who have visited Melasti Beach. Technical analysis of the data used is descriptive analysis is done to obtain the use of space based on a person's activity pattern which is described through behavior mapping. It takes several variables to analyze this research, including actors, activities, flow, time, and form. The results of this study are the activity patterns of Melasti Beach visitors which are divided into 3 types: high-intensity activity patterns occur during the day off, moderate intensity occurs on weekdays and low intensity occurs in the afternoon to evening.